The dinosaurs of Waterhouse Hawkins : an illuminating history of Mr. Waterhouse Hawkins, artist and lecturer - Kerley, Barbara; Selznick, Brian (New York : Scholastic, 2001)
The true story of Victorian artist Benjamin Waterhouse Hawkins, who built life-sized models of dinosaurs in the hope of educating the world about what these awe-inspiring ancient animals and what they were like.
Keywords: Hawkins, B. Waterhouse -- 1807-1894 -- Juvenile literature; Hawkins, B. Waterhouse -- 1807-1894.; Dinosaurs -- Models -- History -- 19th century -- Juvenile literature; Modelmakers -- Great Britain -- Biography -- Juvenile literature; Modelmakers; Dinosaurs